MENAKAR PIDANA KERJA SOSIAL SEBAGAI PARADIGMA BARU KONSEP PEMIDANAAN PERKARA KORUPSI BERBASIS DETERMINISME CULTURAL - Tri Setiawan, Wiranto; Kurnianingsih, Marisa (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
Corruption is a violation of the social, economic and political rights of the wider community. In addition to an environment that still does not have good legal awareness, the typology of corruption is considered a crime that has a high social level so that the perpetrators do not feel deterred even though they have been threatened with serious imprisonment. In the view of cultural determinism, the environment is one of the things that plays a big role so it needs attention. Social work punishment is an alternative concept of punishment that can place corruptors like street crime perpetrators and make perpetrators unite with society. The implication is that the status of perpetrators who have so far been classified as high in social status will be eroded and social work punishment can create moral values that are good for both perpetrators and society. Based on these thoughts, the authors conducted this research. the method used is juridical-normative. The approach used is a statutory approach, a comparative approach and a conceptual approach